Cardiac Injury and Clinical Course of Patients With Coronavirus Disease 2019 - Wang, Yushi; Zheng, Yang; Tong, Qian; Wang, Lihui; Lv, Guorui; Xi, Ziwei; Liu, Wei (Frontiers in Cardiovascular Medicine, 2020)
BACKGROUND: Cardiac injury was recognized as one of the most common critical complications during exacerbation of Coronavirus Disease 2019(COVID-19). The objective of the study was to investigate the impact of cardiac injury on the clinical course of COVID-19, explore its potential mechanism and treatments. METHODS AND RESULTS: A total of 222 hospitalized COVID-19 patients from Wuhan were selected for the study during Feb 10 to March 28 2020. Demographic, laboratory and clinical data on admission and during hospitalization were compared between COVID- 19 patients with or without cardiac injury. On admission, cardiac injury (n=29) was associated with advanced age, more underlying coronary artery disease and lower PaO2. The level of troponin is correlated with inflammation makers (C- reactive Protein, r = 0.348, P < 0.001; interleukin-6, r = 0.558, P < 0.001), and D-Dimer (r = 0.598, P < 0.001). During hospitalization, another 6 patients suffered from cardiac injury and cardiac injury (n=35) leads to more ventilation (invasive, 51.4% vs. 1.6%, P<0.001; non-invasive, 31.4% vs. 1.1%, P<0.001), and death (54.3% vs. 1.1%, P<0.001). Cardiac injury on admission is a predictive factor for mortality (adjusted hazard ratio 4.73, 95% confidence interval 1.35-16.63, p = 0.015). Receiver operating characteristic curve showed that on admission troponin level of 36.35 pg/ml is predictive for mortality with a sensitivity of 73.7% and a specificity of 92.1%. CONCLUSIONS: Cardiac injury complicates the disease course and increases the mortality of COVID-19. Troponin is advised to be checked at admission and during hospitalization for triage, better monitoring, and managing those with COVID-19, especially in sickest patients.